2022
DOI: 10.24874/ti.1131.06.21.08
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Abrasive Wear Parameters of Halloysite Nanotubes Reinforced Silk/Basalt Hybrid Epoxy Composites using Taguchi Approach

Abstract: The demand for environmentally friendly and sustainable materials for nonstructural and structural applications grows by the day. Polymeric composites reinforced with fillers and fibres are considered to have increased strength and desirable wear resistance. Abrasive wear of industrial and agricultural based components are currently one of the most serious issue. Therefore, the current research reports on the influence of Halloysite-Nanotubes (HNTs) loading on the three body abrasive behavior of bidirectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Four parameters viz abrading distance, amount of filler, applied load, as well as silica sand size at three levels were considered. The results showed that abrading distance was the most influential control factor that affected the wear rate [24]. The Taguchi method establishes single parameter significance.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Four parameters viz abrading distance, amount of filler, applied load, as well as silica sand size at three levels were considered. The results showed that abrading distance was the most influential control factor that affected the wear rate [24]. The Taguchi method establishes single parameter significance.…”
Section: Introductionmentioning
confidence: 97%
“…According to the findings, it was demonstrated that sliding distance was the most influential factor affecting the wear rate [23]. Darshan, Suresha, and Jamadar [24] studied the effect of parametric wear rate of Hallosyte nanotube reinforced basalt/silk epoxy composite. Four parameters viz abrading distance, amount of filler, applied load, as well as silica sand size at three levels were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The use of epoxy resin as a matrix material is known to significantly enhance the strength (tensile, flexural, and impact) of mono/hybrid composites (e.g., SiC filled carbon/epoxy and Al2O3 filled carbon/epoxy, SiC filled glass/epoxy) parts [6,7]. In PMCs, Although there is a wide range of matrix/binding materials used (Table 1), epoxy resins offer excellent strength which makes them more practical in aerospace, automotive and marine applications [8].…”
Section: Introductionmentioning
confidence: 99%